Genetic variant associations of human SP-A and SP-D with acute and chronic lung injury - Silveyra, Patricia (2012)
Pulmonary surfactant, a lipoprotein complex, maintains alveolar integrity and plays an important role in lung host defense, and control of inflammation. Altered inflammatory processes and surfactant dysfunction are well described events that occur in patients with acute or chronic lung disease that can develop secondary to a variety of insults. Genetic variants of surfactant proteins, including single nucleotide polymorphisms, haplotypes, and other genetic variations have been associated with acute and chronic lung disease throughout life in several populations and study groups. The hydrophilic surfactant proteins SP-A and SP-D, also known as collectins, in addition to their surfactant-related functions, are important innate immunity molecules as these, among others, exhibit the ability to bind and enhance clearance of a wide range of pathogens and allergens. This review focuses on published association studies of human surfactant proteins A and D genetic polymorphisms with respiratory, and non-respiratory diseases in adults, children, and newborns. The potential role of genetic variations in pulmonary disease or pathogenesis is discussed following an evaluation, and comparison of the available literature.